Changes in habitat use by a deep-diving predator in response to a coastal earthquake. (April 2020) - Guerra, M.; Dawson, S.; Sabadel, A.; Slooten, E.; Somerford, T.; Williams, R.; Wing, L.; Rayment, W.
Abstract: Earthquakes can significantly impact ecosystem function and survivability of marine organisms, however their effect on marine predators remains unknown. In November 2016, a 7.8 magnitude earthquake triggered a 'canyon flushing' event in the submarine canyon of Kaikōura (New Zealand), a year-round foraging ground for sperm whales ( Physeter macrocephalus ). Underwater landslips and turbidity currents caused significant changes to the seafloor and removed large quantities of benthic biomass from the canyon. To investigate the potential impact of the earthquake on habitat use by sperm whales, we used a multi-year dataset to quantify changes in their behaviour, foraging distribution and use of food resources before and after the earthquake. The diving locations and behaviour of individual whales were recorded during summer and winter from January 2014 to January 2018, and samples of sloughed skin were collected for bulk and amino acid specific stable isotope analyses. While blow rates remained unchanged, the mean surface interval between dives was 25% longer for about one year after the earthquake, potentially reflecting increased effort searching for prey. Stable isotope ratios of sperm whale skin provided no evidence for change in diet. However, significant changes in the distribution of core foraging areas indicated shifts in habitat use for at least one year, potentially driven by changes in the seafloor and prey availability following the canyon flushing. Overall, our observations suggested that the earthquake caused alterations in the foraging patterns of sperm whales over a period of at least 12 months. This was the first study to quantify the impact of an earthquake on a marine mammal population, providing new insights into how top predators react and adapt to large-scale events of natural disturbance. Highlights: Sperm whales responded to earthquake-triggered changes in a submarine canyon. Surface intervals between dives increased by 25% for one year after the earthquake. Return to pre-earthquake levels after one year suggested recovery of foraging efficiency. Whales exhibited long-lasting changes in distribution of core foraging areas.